Decentralised Land Tenure, Governance Frameworks, and Rural Development Outcomes: A Technical Review of the Land Use Act (1978) in Nnobi, Nigeria - Benedicta Njideka Okafor (International Journal of Administration and Education (IJAE), 2025)
This study is concerned with the effects of Land Use Act on rural land development in Nigeria with reference to Nnobi as a rural area. Obviously, the law was enacted barley 30 years ago but seems to be a recent innovation to many Nigerians especially in rural areas. The Act conflicts so much with the traditional land proprietary structure in the Southern Nigeria in particular which was predominantly owned by communities. It introduced more controversies and fear from most Nigeria than any previous Act. The importance to the profession of Estate Management of such a radical piece of legislation as the Land Use Act cannot be over emphasized. It is true that laws are for the judiciary to make and interpret, but laws and policies affecting land are also matters in which profession Estate surveyors and valuers as experts on land matters ought to take the front row in offering the benefit of his expertise. Questionnaire and interview methods were mainly used. The purposive sampling technique was used and one hundred twenty (120) respondents. Personal observation was also used to complement the information gathered. The result shows that people especially those living in rural areas are mostly not aware of the Act let alone its provisions on rural land as an avenue for rural land development. This wide ignorant of the Act, by the people has completely retarded the pace of development in our rural areas as well as the socio-economic conditions of the people. After examining the effects of the Act on rural land development in the area concerned and other allied issues, recommendations were made based on the findings for efficient and effective implementation of the Act in rural areas cum rural Lands of Nigeria and if strictly adhered to will go a long way to achieving overall objectives for which the Act was enacted.